Nutrition surveillance of WFP project 2226 for vulnerable group feeding in distressed areas of Bangladesh : report on second phase, 1977-78 - Rahman, Abdur, 1923- (Institute of Nutrition and Food Science, University of Dacca, 1979)
Nutritional monitoring and surveillance study of the food assistance project to Bangladesh of the World Food Programme.